Multiscale evolution of human-water relationship and its influencing factors in the middle and lower reaches of the Yellow River - RAN Zhao, LIU Yansui, GAO Jianhua (Ziyuan Kexue)
[Objective] This study examined the relationship between humans and water from the perspective of supply and demand, and revealed the complicated relationships between humans and water by exploring the supply-demand relationship of water resources, to provide a reference for the balance between supply and demand of water resources and the decision making for sustainable development in the middle and lower reaches of the Yellow River. [Methods] Based on multi-source data and using bivariate spatial autocorrelation, supply-demand ratio, and optimal parameter geographic detector methods, this study explored the scale evolution characteristics and influencing factors of human-water relationship in the middle and lower reaches of the Yellow River. [Results] (1) From 1990 to 2020, the human-water correlation index and the supply-demand ratio in the study region showed a downward trend, indicating that the human-water relationship tended to be tense, and the human-water relationship at the grid scale was superior to that at the county scale. (2) The spatial correlation patterns of humans and water at different scales were mainly Low-Low type, indicating that there was a strong transfer inertia among the spatial interaction types of human-water relationship. The surplus areas were concentrated in the plateau and mountainous areas in the middle reaches and the southeastern area of the lower reaches of the Yellow River, and the deficit areas were located in the wind-blown sand transition zone in northern Shaanxi Province, as well as the Weihe Plain, the Shanxi Basin, the Yellow River alluvial plain, and the northwestern plain of Shandong Province. (3) The multiscale evolution process of the human-water relationship is mainly the result of the interaction and coupling of climate change, human activities, landscape pattern, and topography. Human activity is always the most stable and active factor at multiple scales. The influence of climate change and landscape pattern on human-water relationship is different at different scales. [Conclusion] In view of the tense relationship between humans and water in the middle and lower reaches of the Yellow River, it is urgent to develop a water-saving and efficient modern agricultural system, implement the development strategy of “determining production by water”, and effectively coordinate the conflicts between humans and water through landscape planning.